Big Food, Nutritionism, and Corporate Power. Issue 4 (7th June 2017) - Clapp, Jennifer; Scrinis, Gyorgy
Abstract: Big Food corporations have capitalized on nutritionism—the reduction of food's nutritional value to its individual nutrients—as a means by which to enhance their power and position in global processed and packaged food markets. Drawing on the literatures on nutrition and corporate power, we show that Big Food companies have used nutritional positioning to bolster their power and influence in the sector. Through lobbying and participation in nutritionally focused public–private partnerships, they have directly sought to influence policy and governance. Through market dominance in the nutritionally enhanced foods sector, and participation in nutrition-focused rule-setting activities in agrifood supply chains, they have gained power to influence policy agendas. And they have used public outreach and the media to present their views on the nutritional aspects of their products, which shapes public perceptions and the broader regulatory environment. Together, these strategies have enhanced the power of Big Food firms to influence policies in the food sector.